Last paper standing: a century of competition between the the Denver Post and the Rocky Mountain News - Ward, Ken J., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2023)
History of competition between the Denver Post and Rocky Mountain News, 1859-2009. Details founding of both papers, including key figures and strategies, and their competition for Denver's newspaper market until the News' closing in 2009.--Provided by publisher.
Keywords: Denver post -- History; American newspapers -- Colorado -- Denver -- History; Rocky Mountain news -- History